2014
DOI: 10.2147/jpr.s66414
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation with implanted epidural paddle lead relieves chronic axial low back pain

Abstract: IntroductionSpinal cord stimulation (SCS) provides significant relief for lumbosacral radiculopathy refractory to both medical and surgical treatment, but historically only offers limited relief for axial low back pain (LBP). We aim to evaluate the response of chronic axial LBP treated with SCS using a surgically implanted epidural paddle lead.Materials and methodsThis is a retrospective review of a consecutive series of patients with exclusive LBP or predominant LBP associated with lower extremity (LE) pain e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Importantly, it is not currently feasible to target specific motor pools via dorsal ES. In fact, it is likely that ES preferentially activates central pattern generator circuitry, which limits its therapeutic potential (Bareyre et al, 2004 ; Taccola et al, 2017 ) Conversely, scarring and functional stability are major barriers for clinical translation of intraparenchymal stimulation techniques, whereas ES has been widely applied in the clinic with favorable outcomes (Stidd et al, 2014 ).…”
Section: Leveraging Neuronal Activity-associated Mechanisms To Promotmentioning
confidence: 99%
“…Importantly, it is not currently feasible to target specific motor pools via dorsal ES. In fact, it is likely that ES preferentially activates central pattern generator circuitry, which limits its therapeutic potential (Bareyre et al, 2004 ; Taccola et al, 2017 ) Conversely, scarring and functional stability are major barriers for clinical translation of intraparenchymal stimulation techniques, whereas ES has been widely applied in the clinic with favorable outcomes (Stidd et al, 2014 ).…”
Section: Leveraging Neuronal Activity-associated Mechanisms To Promotmentioning
confidence: 99%
“…A case series found that 89% (eight out of nine) of patients had >50% relief of chronic axial LBP with a mean follow-up of 19.9 months after SCS implantation. [ 34 ] As mentioned above, we believed our patient would gain relief from surgical decompression using a laminectomy and that a surgical paddle lead would provide a palliative pain control of chronic LBP and leg pain as a result of FBSS. Even so, laminectomy or laminotomy is an invasive procedure, and the benefits of surgical paddle leads are gained with durable pain coverage and reduced likelihood of lead migration.…”
Section: Discussionmentioning
confidence: 93%
“…Studies show slightly more morbidity with paddle leads but better short-term results. However, long-term follow-up at three years shows similar outcomes [ 15 , 16 ]. The results of spinal cord stimulation for FBSS can be affected by the experience and specialty of the implanter [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of spinal cord stimulation for FBSS can be affected by the experience and specialty of the implanter [ 17 ]. Using a single lead targeting primarily axial lumbar pain may not provide sufficient stimulation coverage for patients who also have peripheral neuropathic pain affecting the lower legs and feet or lateralized pain after joint replacement [ 14 , 16 , 18 ]. Most battery systems allow the use of two leads which provides the ability to place two separate electrode arrays, one targeting the axial lumbar spine pain and the other targeting the peripheral neuropathic pain or more lateral joint pain.…”
Section: Discussionmentioning
confidence: 99%